Experimental verification of the spectral shift between near- and far-field peak intensities of plasmonic infrared nanoantennas - Alonso-González, Pablo; Albella, P.; Neubrech, Frank; Huck, Christian; Chen, J.; Golmar, F.; Casanova, F.; Hueso, L. E.; Pucci, Annemarie; Aizpurua, J.; Hillenbrand, R. (Physical review letters, 2013)
Theory predicts a distinct spectral shift between the near- and far-field optical response of plasmonic antennas. Here we combine near-field optical microscopy and far-field spectroscopy of individual infrared-resonant nanoantennas to verify experimentally this spectral shift. Numerical calculations corroborate our experimental results. We furthermore discuss the implications of this effect in surface-enhanced infrared spectroscopy.
Gesehen am 12.05.2021